PUBLIC ATTITUDES TO VISITING SWIMMING POOLS AND WATER PARKS - Solomakha, Kseniia (The Ukrainian Scientific Medical Youth Journal, 2021)
Recreational activities by the water are quite popular today. Swimming is one of the most popular ways of spending free time and sports activities, also swimming has few contraindications and, in general, is usually a good idea at any age. In our country we have a wide network of various water complexes from small spas, baths, swimming pools to large-scale water parks. At the same time, we can notice that visiting swimming pools, water parks, spa centers and other water complexes is associated with an increased risk of infectious and parasitic diseases, injuries, manifestations of allergic reactions in visitors, therefore, constant monitoring of the operation of such complexes is mandatory, as well as control at the design phase, because it`s easier to prevent some moments than to correct them in the future. Water treatment methods occupy an important place in the system of monitoring the parameters of the internal environment of the water complex and the quality of water in the pools, and these methods included filtration, disinfection, and water circulation conditions. The operation of the pool is inevitably associated with water pollution: it can be with pathogenic microorganisms, organic substances and the remains of cosmetics which enter the water with the swimmers. In this case, an insufficient level of culture of visitors, especially young children, who, due to their age, cannot control their physiological needs, also play a negative role. An important point is also the long-term use of water and not frequent sanitization of the pools (with a full drain of water). The unsatisfactory sanitary state of these complexes is also facilitated by the fact that the medical examination of visitors is rather formal, and in spa centers and water parks, which are most often visited by completely different people every day, they are not needed at all, as well as a certificate of good health; that’s why the implementation of sanitary and hygienic standards and modes of operation of pools and other water complexes is mandatory, in practice, unfortunately, in our country it completely depends on the awareness of business owners. However, the issue of safety while visiting such water complexes is important. The main purpose of our research was to analyze how visitors subjectively assess the safety of visiting water complexes, and to identify the main complaints that arise in those complexes where the main method of water disinfection is chlorination. Materials and methods: we did a cross-sectional survey among visitors of swimming pools and water parks during the period from August 2019 to December 2020 as well as the water samples were collected and analyzed. The practical significance of the obtained results was to identify the main trends, problems, and critical moments from the subjective point of view of the visitors and to be able to assess the importance of hygienic education while visiting water complexes. Conclusions: in general, we note the lack of knowledge and awareness of hygiene issues before and after visiting the swimming pool (water park), which should be noted by professionals responsible for the health of visitors of different water complexes.